T cell-intrinsic protein kinase D3 is dispensable for the cells’ activation - Koutník, Jiří; Leitges, Michael; Siegmund, Kerstin (Frontiers in Immunology, 2022)
Protein kinases D (PKDs) are implicated in T cell receptor (TCR) signaling. Of the two T cell expressed isoforms PKD2 and PKD3, however, only the former one is rather well understood in this immune cell type. Recently, we have observed a putative hyper-phenotype of T cells from conventional PKD3-knockout mice, which we explained as a secondary effect due to a skewed T cell compartment from naïve towards effector/memory T cells already under steady state conditions. Nonetheless, to this end it is not clear whether these aberrations are mediated by a T cell intrinsic or extrinsic function of PKD3. To address this question, we have investigated mice lacking PKD3 specifically in the T cell compartment. We could show that T cells from CD4-Cre driven conditional knockout mice did not phenocopy the ones from conventional PKD3-knockout mice. In brief, no skewing in the T cell compartment of peripheral lymphoid organs, no hyper-activation upon stimulation in vitro or in vivo as well as no aberrations in follicular helper T cells (TFH) upon immunization were observed. Hence, although PKD3 is strongly regulated upon TCR stimulation, in T cells this kinase seems to be dispensable for their activation. The described skewing in the T cell compartment of conventional PKD3-deficient mice seems to be mediated by T cell-extrinsic mechanisms, thus once more emphasizing the importance of cell type-specific mouse models.